2003
DOI: 10.1097/01.ju.0000092780.85876.de
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Sparing Surgery for Renal Cell Carcinoma and von Hippel-Lindau’s Disease: A Single Center Experience

Abstract: Nephron sparing surgery is effective and, when feasible, it need not be called into question. However, it may probably be superseded by less invasive techniques for tumors less than 20 mm diagnosed early after these techniques have been validated in long-term trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…1,24 Although the mean age at clinical diagnosis is B40 years, asymptomatic tumours are frequently detected earlier (though rarely below 16 years). [24][25][26] Histopathological examination of kidneys removed from VHL patients shows large numbers of microscopic tumour foci in apparently normal parenchyma that explain the high risk of multiple and bilateral RCC in VHL disease. 27 Multiple renal cysts are common in VHL disease and although they rarely compromise renal function, the lining epithelium may be dysplastic or show carcinoma-in-situ and give rise to RCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,24 Although the mean age at clinical diagnosis is B40 years, asymptomatic tumours are frequently detected earlier (though rarely below 16 years). [24][25][26] Histopathological examination of kidneys removed from VHL patients shows large numbers of microscopic tumour foci in apparently normal parenchyma that explain the high risk of multiple and bilateral RCC in VHL disease. 27 Multiple renal cysts are common in VHL disease and although they rarely compromise renal function, the lining epithelium may be dysplastic or show carcinoma-in-situ and give rise to RCC.…”
Section: Introductionmentioning
confidence: 99%
“…28 After establishing the growth rate, an individual renal lesion can kept under regular surveillance until it reaches 3 cm diameter when partial nephrectomy (or an alternative technique such as radiofrequency ablation) is performed. 29,25 At the time of surgery any additional smaller lesions that are accessible are removed in order to delay the need for reoperation. Follow-up of VHL patients treated by nephron-sparing surgery reveals a high incidence of local recurrence from new primary tumours, but a low risk of distant metastasis 30 whereas about 25% of VHL patients with more advanced RCC (43 cm) develop metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Herring et al reported their 10 year experience of managing 50 patients none of whom required dialysis and only one developed metastatic disease [42]. Roupert and Walther et al reported similarly good results with no metastatic progression [36,43].…”
Section: Von Hippel-lindau Syndromementioning
confidence: 55%
“…1,2,9 RCC is considered a leading cause of mortality in VHL syndrome, and the average age at clinical diagnosis is approximately 60 y old. 2,10 The family in this study had 3 family members exhibiting VHL manifestations with initial stages of central nervous system hemangioblastomas; however, none of them had any ocular symptoms. Moreover, the brother and his sister were considered as subclinical pheochromocytoma or normotensive pheochromocytoma because of serendipitous discoveries by radiologic examination 11 and negative endocrine subjects, including urine VMA 12 .…”
Section: Discussionmentioning
confidence: 99%